The relationship between organizational characteristics and entrepreneurial orientation among employees of cement manufacturers in Johor - Shathees, Baskaran (2014)
The purpose of the study is twofold. First, to examine the relationship between organizational characteristics and entrepreneurial orientation, and second to examine the mediating effect of knowledge management enabler between organizational characteristics and entrepreneurial orientation among employees of cement manufacturers in the state of Johor. Fifteen hypotheses were formulated; that there is significant relationships between organizational characteristics (work discretion, resource/time availability, management support and reward/reinforcement) and entrepreneurial orientation (innovativeness, risk- taking and proactiveness) and knowledge management enabler mediates the relationship between organizational characteristics and entrepreneurial orientation. The data for the quantitative study were collected from an online internet-based web survey questionnaire through a simple random sampling method. The population consisted of all employees who were working in the three cement manufacturing companies under study. The total number of respondents was 257 out of 300 employees randomly selected. An overall response rate of 70.4 per cent was obtained. Multiple regression analysis was utilized to analyze the survey data while ensuring that all the necessary assumptions are met. The results indicated that nine out of fifteen hypotheses tested were supported. Generally, the study provides empirical evidence that there is significant relationship between organizational characteristics and entrepreneurial orientation. Knowledge management enabler was also found to partially mediate the relationship between organizational characteristics and entrepreneurial orientation. Theoretical and managerial contributions were discussed as well as study limitations and suggestions for future research.